Towards a physiological and physical model of sprint kayaking; a current review of literature - Dingley, A.; Lee, S.; Lum, D.; Franky, H.; Tan, Y.; Fernandes, J. T. F. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In sprint kayaking, a tenth of a second can separate those who win a medal (e.g. male 200m finals at the 2020 Olympics). Therefore, practitioners need a comprehensive understanding of the variables which influence sprint kayaking performance (e.g. physiological and physical characteristics). Although studies have investigated how physiological and physical attributes may influence sprint kayaking performance, there is currently no review study conducted to draw the literature together. The aim of this study was to critically review the physiological and physical determinants of sprint kayaking performance. A secondary aim was to inform future research and provide guidelines for practitioners.